WALKER, Charles (2015). La rebelión de Tupac Amaru. Lima: IEP. - Marcelo Doroteo, Raúl (2020)
Many books and articles have been written about the Tupacamarist rebellion of the 18th century. Some are characterized by becoming apologies for the rebellion, but others are eminently of academic dissemination. The text of Walker that I review - one more of that abundant and plural bibliography - is, of course, an academic writing.